Elucidating the genetic variability and diversity among Chilli (Capsicum annuum L.) genotypes for growth and yield-related traits under sodic soil in Tamil Nadu through a multivariate approach - Sidhdharth, G; Suresh, J; Meenakshisundaram, P; Saravanapandian, P; Parameswari, K; Padmadevi, K; Ahamed, S A; Jegadeeswari, V; Vijayalatha, K R (Plant Science Today, 2025)
Chilli (Capsicum annum L.) is a commercially important crop cultivated for both vegetable and spice uses. This study aims to explore the genetic diversity of thirty genotypes under sodic soil conditions at HC&RI(W), Tiruchirappalli, over two seasons (Kharif and Rabi) in 2023-2024. Analysis of variance (ANOVA) revealed significant variability among the genotypes for thirteen different quantitative and qualitative parameters evaluated under sodicity. The phenotypic coefficient of variation was higher than the genotypic coefficient, suggesting minimal environmental influence on the traits. Most parameters exhibited high heritability, with several (e.g., number of days for first picking, seeds per pod and chlorophyll stability index) showing high genetic advance, indicating the potential for improvement through direct selection. Principal Component Analysis (PCA) reduced the genotypes to thirteen components, with the first four accounting for 73.24% of the variability. The genotypes are divided into five clusters based on the Euclidean distance through Mahalanobsis D2 analysis grouped the genotypes into five clusters, each cluster demonstrating superiority in specific traits suitable for further breeding. Notably, the high inter-cluster distance between clusters IV & V and III & V indicates diverse genetic material that could be valuable for hybridization programs aimed at improving sodic soil tolerance.